2013
DOI: 10.1021/jp407096p
|View full text |Cite
|
Sign up to set email alerts
|

Sonohydrothermal Synthesis of Nanostructured (Ce,Zr)O2 Mixed Oxides with Enhanced Catalytic Performance

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Moreover, its surface area and nanosize rarely changed after being calcined at 500 °C. Recently, Nikitenko et al [124] prepared Ce0.5Zr0.5O2 nanocrystallite mixed oxide with external mesopores using simultaneous sonohydrothermal treatment. The obtained material exhibited higher surface area than the similar material prepared by an ultrasonically assisted CP method.…”
Section: Sonochemical Synthesis Methodsmentioning
confidence: 99%
“…Moreover, its surface area and nanosize rarely changed after being calcined at 500 °C. Recently, Nikitenko et al [124] prepared Ce0.5Zr0.5O2 nanocrystallite mixed oxide with external mesopores using simultaneous sonohydrothermal treatment. The obtained material exhibited higher surface area than the similar material prepared by an ultrasonically assisted CP method.…”
Section: Sonochemical Synthesis Methodsmentioning
confidence: 99%
“…The synthesis strategies of ceria‐zirconia solid solutions are similar to the aforementioned methods for preparing ceria nanocrystals such as hydrothermal, sol‐gel and sonochemical methods, etc. Our group developed a mild urea hydrolysis‐based hydrothermal method to prepare Ce 1– x Zr x O 2 ( x = 0–0.8) nanopowders with superior structural homogeneity and superior thermal stability and validated a strong correlation between lattice strain and OSC value in the Ce 1– x Zr x O 2 solid solutions .…”
Section: Tuning the Composition Of Ceria‐based Composite Nanocatalystsmentioning
confidence: 99%
“…Recently it was shown that such sonohydrothermal treatment (SHT) accelerates the crystallization and improves the catalytic performance of nanocrystalline metal oxides. 11 The experimental details about SHT reactor are presented in Supporting Information ( Figure S1). …”
Section: Vis/nirmentioning
confidence: 99%